Impregnating emulsion for scratch-resistant formaldehyde-free impregnated decorative paper and preparation method of impregnating emulsion
By introducing nano-apatite and organosilicon-modified polyurethane-acrylate resin into impregnated decorative paper, the problem of insufficient scratch resistance of formaldehyde-free impregnated decorative paper surface is solved, achieving both formaldehyde-free and scratch-resistant effects.
Patent Information
- Application Number
- CN202511176969.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-09-30
- Filing Date
- 2025-08-21
- Publication Date
- 2025-11-14
AI Technical Summary
The existing formaldehyde-free impregnated decorative paper has insufficient scratch resistance and is easily scratched during the pressing process, affecting the surface quality.
Nano-apatite is used as a filler dispersed in the resin and combined with silicone-modified polyurethane-acrylate resin to improve the surface hardness of the impregnated decorative paper. By introducing the combination of nano-apatite and silicone-modified polyurethane-acrylate resin, the scratch resistance of the adhesive system is increased.
It achieves improved surface hardness and scratch resistance in formaldehyde-free impregnated decorative paper, while eliminating the release of free formaldehyde and meeting relevant national standards.
Smart Images

Figure CN120945729A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of materials processing technology, specifically to an impregnation emulsion for scratch-resistant, formaldehyde-free impregnated decorative paper and its preparation method. Background Technology
[0002] Impregnated decorative paper is made by printing and impregnating decorative base paper with resin. It is widely used for surface decoration of engineered wood products, accounting for approximately 65% of the surface decoration material market. It not only beautifies engineered wood products but also imparts excellent surface properties, including stain resistance, water vapor resistance, and scratch resistance. Historically, urea-formaldehyde resin or melamine-formaldehyde resin have been commonly used for impregnation. These resins release formaldehyde during production and use, posing a certain hazard to workers and consumers. Producing formaldehyde-free decorative engineered wood products is an important direction for future development. Currently, engineered wood products made with soybean protein glue, lignin glue, or isocyanate glue have been developed. The Wood Industry Research Institute of the Chinese Academy of Forestry (ZL202010394895.7), the Forestry New Technology Research Institute of the Chinese Academy of Forestry (ZL202010394935.8), and Guangdong Tianyuan Huibang New Material Co., Ltd. (ZL201811302724.6) have developed polyurethane / polyacrylate resins with low polymerization degree, high permeability, and high solids content. Using monomers with active groups such as hydroxyl / amine groups and modifying agents, they have constructed impregnating resin systems for formaldehyde-free impregnated paper with different functions, producing formaldehyde-free impregnated decorative paper products. These products exhibit good finishing effects on various engineered wood substrates. However, these formaldehyde-free impregnated decorative paper products suffer from insufficient surface scratch resistance, easily scratching the surface during the pressing and dragging process, affecting surface quality. Therefore, the preparation of a scratch-resistant formaldehyde-free impregnated decorative paper is essential. Summary of the Invention
[0003] To address the shortcomings of existing technologies, the present invention aims to provide a scratch-resistant, formaldehyde-free impregnating emulsion for decorative paper and its preparation method. The present invention uses nano-apatite as a filler dispersed in the resin. Therefore, the introduced filler increases the surface hardness of the impregnated decorative paper with minimal impact on viscosity, thereby achieving scratch resistance.
[0004] To achieve the above objectives, the present invention provides the following technical solution: A scratch-resistant, formaldehyde-free impregnating emulsion for decorative paper comprises the following components: The ingredients are: 50-70 parts of silicone-modified polyurethane-acrylate resin, 30-40 parts of acrylamide monomers, 2-8 parts of nano-hydroxyapatite, 2-5 parts of curing agent, 0.01-0.03 parts of defoamer, and 0.01-0.05 parts of substrate wetting agent.
[0005] The preparation method of silicone-modified polyurethane-acrylate resin includes the following steps: S1. Add 20-40 parts of diol and 16-40 parts of diisocyanate to a reactor equipped with a stirrer and reflux device, and carry out a prepolymerization reaction under the protection of 99.9% nitrogen gas at a reaction temperature of 40-60℃ for 0.5-1h to obtain a polyurethane prepolymer. S2. Heat the polyurethane prepolymer to 65-80℃, add the chain extender dropwise over 10-20 minutes, and allow the chain extension reaction to proceed for 0.5-1.5 hours while stirring at 50-100 rpm. Then cool the prepolymer to 40-60℃ and add 8-12 parts of hydrophilic agent over 25-30 minutes. This step of the reaction should take 0.5-1.5 hours. S3. Cool to room temperature, add 0.1-0.5 parts of glacial acetic acid for neutralization, and simultaneously use 1-3 parts of acetone to reduce viscosity. Once the viscosity is suitable, add 15-20 parts of deionized water and 1.7-3.3 parts of organosilicon, and shear at high speed (2000-4000 r / min). Evaporate and remove acetone to obtain organosilicon-modified polyurethane emulsion. The solid content of the emulsion is 33-37%, the particle size is 50-100 nm, the viscosity is 50-100 cp, and the molecular weight is 500-2000. S4. Add 0.1-0.2 parts ammonia water, 25-40 parts deionized water, 10-15 parts soft acrylate monomer, 20-25 parts hard acrylate monomer, 1.7-3.3 parts hydroxy acrylate monomer, 0.03-0.1 parts initiator, 5-10 parts anionic surfactant and 6-14 parts nonionic surfactant to the reactor. Maintain a stirring speed of 150-200 r / min at room temperature and react for 7-10 min. Stop the reaction immediately after the color turns bluish to obtain a polyacrylate preemulsion. S5. Mix the remaining 20-25 parts of soft acrylate monomer, 20-25 parts of hard acrylate monomer, and 3.3-6.7 parts of hydroxyl acrylic monomer evenly. Under the condition of 75-85℃, add them dropwise to the polyacrylate preemulsion along with the remaining initiator. While maintaining a stirring speed of 150-240r / min, heat to 75-85℃ and start adding the remaining 3.3-6.7 parts of organosilicon. The addition is completed in 30-40min. After completion, keep the reaction temperature for 15-30min to obtain the organosilicon modified acrylate emulsion. The solid content of the emulsion is 33-37%, the particle size is 50-100nm, the viscosity is 20-100cp, and the molecular weight is 300-2000. S6. Mix the prepared silicone-modified polyurethane emulsion and silicone-modified polyacrylate emulsion, and react them at a temperature of 50-70℃ for 25-30 minutes to obtain silicone-modified polyurethane-acrylate resin.
[0006] Preferably, the acrylamide monomer is one or more of acrylamide, hydroxymethylacrylamide, and hydroxyethylacrylamide; the curing agent is preferably aziridine; and the defoamer is preferably polyether silicone oil.
[0007] Preferably, the nano-hydroxyapatite has a particle size of 20-80 nm.
[0008] Preferably, the silicone-modified polyurethane-acrylate resin comprises the following components by weight: 16-40 parts diisocyanate, 20-40 parts diol, 40-50 parts hard acrylate monomer, 30-40 parts soft acrylate monomer, 5-10 parts hydroxyl acrylic monomer, 0.1-0.5 parts glacial acetic acid, 3-8 parts chain extender, 8-12 parts hydrophilic agent, 0.1-0.3 parts initiator, 5-10 parts anionic surfactant, 6-14 parts nonionic surfactant, 5-10 parts silicone, 40-60 parts water, 0.1-0.2 parts ammonia, and 1-3 parts acetone.
[0009] Preferably, the diol is one or more of polyethylene glycol, polypropylene glycol, and polyester diol; the diisocyanate includes one or more of isophorone diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, hexamethylene diisocyanate, and lysine diisocyanate.
[0010] Preferably, the hard acrylate monomers include one or more of methyl methacrylate, acrylic acid, methacrylic acid, and acrylonitrile; the soft acrylate monomers include one or more of methyl acrylate, butyl acrylate, and n-octyl acrylate; and the hydroxyacrylate monomers are one of hydroxyethyl acrylate, hydroxybutyl acrylate, and dihydroxypropyl acrylate.
[0011] Preferably, the chain extender is one of ethylene glycol, propylene glycol, and 1,4-butanediol; the hydrophilic agent is N-methyldiethanolamine; the initiator is persulfate, preferably one of sodium persulfate, ammonium persulfate, and potassium persulfate; and the anionic surfactant is sodium dodecyl sulfate.
[0012] Preferably, the nonionic surfactant is one or more of NP-15, A-103, and X-405.
[0013] Preferably, the organosilicon comprises two or more of tetraethoxysilane, vinyltrimethoxysilane, and methylγ-mercaptopropyldimethoxysilane.
[0014] A method for preparing an impregnation emulsion for scratch-resistant, formaldehyde-free impregnated decorative paper includes the following steps: Add 30-40 parts of acrylamide monomers, 2-8 parts of nano-hydroxyapatite, 2-5 parts of curing agent, 0.01-0.03 parts of defoamer, and 0.01-0.05 parts of substrate wetting agent to silicone-modified polyurethane-acrylate resin. Stir for 8-10 minutes at room temperature and 100-150 r / min, and let stand to obtain scratch-resistant formaldehyde-free impregnated decorative paper impregnation emulsion.
[0015] Compared with the prior art, the beneficial effects of the present invention are: 1. None of the components of the prepared adhesive contain free formaldehyde, and the adhesive product releases no free formaldehyde, thus achieving formaldehyde-free impregnation of decorative paper.
[0016] 2. Modifying polyurethane-acrylate emulsion with organosilicon and appropriately increasing its solid content can improve the adhesive absorption of impregnated decorative paper. Introducing acrylamide monomers can enable rapid penetration into the interlayer of the decorative base paper at room temperature and self-crosslinking and curing at high temperature, thereby increasing the interlayer bonding strength of the impregnated decorative paper.
[0017] 3. Nano-apatite is dispersed into the resin as a filler. The introduced filler increases the surface hardness of the impregnated decorative paper without significantly affecting the viscosity, thereby achieving a scratch-resistant effect. Attached Figure Description
[0018] Figure 1 This diagram illustrates the preparation steps of the silicone-modified polyurethane-acrylate resin of this invention. Detailed Implementation
[0019] The present invention will now be clearly and completely described in conjunction with embodiments thereof. Obviously, the described embodiments are merely some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0020] Please see Figure 1 The present invention provides a technical solution: Example 1 A method for preparing an impregnation emulsion for scratch-resistant, formaldehyde-free impregnated decorative paper: S1. Add 20 parts of polyethylene glycol and 16 parts of isophorone diisocyanate to a reactor equipped with a stirrer and a reflux device, and carry out a prepolymerization reaction under the protection of 99.9% nitrogen gas at a reaction temperature of 40°C for 0.5 h to obtain a polyurethane prepolymer.
[0021] S2. Heat the polyurethane prepolymer to 65°C, add ethylene glycol dropwise to the prepolymer over 10 min, the chain extension reaction lasts 0.5 h, and the stirring speed is 50 r / min. Then cool down to 40°C and add 8 parts of N-methyldiethanolamine over 25 min, the reaction lasts 0.5 h.
[0022] S3. Cool to room temperature, add 0.1 parts of glacial acetic acid for neutralization, and simultaneously use 1 part of acetone to reduce viscosity. Once the viscosity is suitable, add 15 parts of deionized water and 1.7 parts of organosilicon (composed of 1 part of tetraethoxysilane and 0.7 parts of methyl γ-mercaptopropyl dimethoxysilane), and shear at high speed (2000 r / min). Evaporate and remove acetone to obtain the organosilicon-modified polyurethane emulsion. The emulsion has a solid content of 33%, a particle size of 50 nm, a viscosity of 50 cp, and a molecular weight of 500.
[0023] S4. Add 0.1 parts ammonia water, 25 parts deionized water, 10 parts methyl acrylate, 20 parts methyl methacrylate, 1.7 parts hydroxyethyl acrylate, 0.03 parts sodium persulfate, 5 parts sodium dodecyl sulfate and 6 parts NP-15 to the reactor, and keep the stirring speed at 150 r / min at room temperature for 7 min. Stop the reaction immediately after the color turns blue to obtain a polyacrylate preemulsion. S5. Mix the remaining 20 parts of methyl acrylate, 20 parts of methyl methacrylate, and 3.3 parts of hydroxyethyl acrylate evenly. At 75°C, add the remaining sodium persulfate dropwise to the polyacrylate pre-emulsion simultaneously. While maintaining a stirring speed of 150 r / min, raise the temperature to 75°C and begin to add the remaining 3.3 parts of organosilicon (composed of 1.5 parts of tetraethoxysilane and 1.8 parts of methyl γ-mercaptopropyl dimethoxysilane). The addition is completed in 30 min. After completion, maintain the temperature for 15 min to obtain the organosilicon-modified acrylate emulsion. The solid content of the emulsion is 33%, the particle size is 50 nm, the viscosity is 20 cp, and the molecular weight is 300.
[0024] S6. Mix the prepared silicone-modified polyurethane emulsion and silicone-modified polyacrylate emulsion, and react at 50°C for 25 minutes to obtain silicone-modified polyurethane-acrylate resin.
[0025] S7. Add 30 parts acrylamide, 2 parts nano hydroxyapatite, 2 parts PZ-33, 0.01 parts BYK-028, and 0.01 parts BYK-346 to silicone-modified polyurethane-acrylate resin. Stir for 8 minutes at room temperature and 100 r / min, and let stand to obtain scratch-resistant formaldehyde-free impregnated decorative paper impregnation emulsion.
[0026] The base paper is impregnated and dried using the above-mentioned anti-scratch formaldehyde-free impregnated decorative paper impregnation emulsion to obtain impregnated film paper; the impregnated decorative paper is hot-pressed onto the surface of the artificial board to obtain decorative paper-faced artificial board.
[0027] Example 2 A method for preparing an impregnation emulsion for scratch-resistant, formaldehyde-free impregnated decorative paper: S1. Add 40 parts of polypropylene glycol and 40 parts of diphenylmethane diisocyanate to a reactor equipped with a stirrer and a reflux device, and carry out a prepolymerization reaction under the protection of 99.9% nitrogen gas at a reaction temperature of 60°C for 1 hour to obtain a polyurethane prepolymer.
[0028] S2. Heat the polyurethane prepolymer to 80°C, add propylene glycol dropwise over 20 minutes, and allow the chain extension reaction to proceed for 1.5 hours while stirring at 100 rpm. Then cool the prepolymer to 60°C and add 12 parts of N-methyldiethanolamine over 30 minutes. This step of the reaction takes 1.5 hours.
[0029] S3. Cool to room temperature, add 0.5 parts of glacial acetic acid for neutralization, and simultaneously use 3 parts of acetone to reduce viscosity. Once the viscosity is suitable, add 20 parts of deionized water and 3.3 parts of organosilicon (composed of 1.3 parts of tetraethoxysilane and 2 parts of vinyltrimethoxysilane), and shear at high speed (4000 r / min). Evaporate and remove acetone to obtain the organosilicon-modified polyurethane emulsion. The emulsion has a solid content of 37%, a particle size of 100 nm, a viscosity of 100 cp, and a molecular weight of 2000.
[0030] S4. Add 0.2 parts ammonia water, 40 parts deionized water, 15 parts butyl acrylate, 25 parts acrylic acid, 3.3 parts hydroxybutyl acrylate, 0.1 parts ammonium persulfate, 10 parts sodium dodecyl sulfate and 14 parts A-103 to the reactor, and keep the stirring speed at 200 r / min at room temperature for 10 min. Stop the reaction immediately after the color turns blue to obtain a polyacrylate preemulsion. S5. Mix the remaining 25 parts butyl acrylate, 25 parts acrylic acid, and 6.7 parts hydroxybutyl acrylate evenly. At 85°C, add the mixture dropwise to the polyacrylate preemulsion along with the remaining ammonium persulfate. While maintaining a stirring speed of 240 r / min, raise the temperature to 85°C and begin adding the remaining 6.7 parts organosilicon (composed of 3 parts tetraethoxysilane and 3.7 parts vinyltrimethoxysilane). The addition is completed in 40 min. After completion, maintain the temperature for 30 min to obtain the organosilicon-modified acrylate emulsion. The solid content of the emulsion is 37%, the particle size is 100 nm, the viscosity is 100 cp, and the molecular weight is 2000.
[0031] S6. Mix the prepared silicone-modified polyurethane emulsion and silicone-modified polyacrylate emulsion, and react at 70°C for 30 minutes to obtain silicone-modified polyurethane-acrylate resin.
[0032] S7. Add 40 parts of hydroxymethylacrylamide, 8 parts of nano-hydroxyapatite, 5 parts of PZ-33, 0.03 parts of BYK-028, and 0.05 parts of BYK-346 to silicone-modified polyurethane-acrylate resin. Stir for 10 minutes at room temperature and 150 r / min, and let stand to obtain scratch-resistant formaldehyde-free impregnating emulsion for decorative paper.
[0033] The base paper is impregnated and dried using the above-mentioned anti-scratch formaldehyde-free impregnated decorative paper impregnation emulsion to obtain impregnated film paper; the impregnated decorative paper is hot-pressed onto the surface of the artificial board to obtain decorative paper-faced artificial board.
[0034] Example 3 A method for preparing an impregnation emulsion for scratch-resistant, formaldehyde-free impregnated decorative paper: S1. Add 30 parts of polyester diol and 30 parts of dicyclohexylmethane diisocyanate to a reactor equipped with a stirrer and a reflux device, and carry out a prepolymerization reaction under the protection of 99.9% nitrogen gas at a reaction temperature of 50°C for 0.7 h to obtain a polyurethane prepolymer.
[0035] S2. Heat the polyurethane prepolymer to 70°C, add 1,4-butanediol dropwise over 15 minutes, and allow the chain extension reaction to proceed for 1 hour while stirring at 70 rpm. Then cool the prepolymer to 45°C and add 9 parts of N-methyldiethanolamine over 27 minutes. This step takes 1 hour.
[0036] S3. Cool to room temperature, add 0.2 parts of glacial acetic acid for neutralization, and simultaneously use 2 parts of acetone to reduce viscosity. Once the viscosity is suitable, add 16 parts of deionized water and 2 parts of organosilicon (composed of 1 part of methyl γ-mercaptopropyl dimethoxysilane and 1 part of vinyltrimethoxysilane), and shear at high speed (3000 r / min). Evaporate and remove acetone to obtain the organosilicon-modified polyurethane emulsion. The emulsion has a solid content of 35%, a particle size of 75 nm, a viscosity of 70, and a molecular weight of 1500.
[0037] S4. Add 0.15 parts ammonia water, 30 parts deionized water, 12 parts n-octyl acrylate, 22 parts methacrylic acid, 2 parts dihydroxypropyl acrylate, 0.05 parts potassium persulfate, 7 parts sodium dodecyl sulfate and 9 parts X-405 to the reactor, and keep the stirring speed at 175 r / min at room temperature for 8 min. Stop the reaction immediately after the color turns blue to obtain a polyacrylate preemulsion. S5. Mix the remaining 22 parts of n-octyl acrylate, 22 parts of methacrylic acid, and 4 parts of dihydroxypropyl acrylate evenly. At 79°C, add the mixture dropwise to the polyacrylate preemulsion along with the remaining potassium persulfate. While maintaining a stirring speed of 200 r / min, raise the temperature to 79°C and begin to add the remaining 4 parts of organosilicon (composed of 2 parts of methyl γ-mercaptopropyl dimethoxysilane and 2 parts of vinyltrimethoxysilane). The addition is completed in 35 min. After completion, maintain the temperature for 17 min to obtain the organosilicon-modified acrylate emulsion. The solid content of the emulsion is 35%, the particle size is 75 nm, the viscosity is 50 cp, and the molecular weight is 900.
[0038] S6. The prepared silicone-modified polyurethane emulsion and silicone-modified polyacrylate emulsion are mixed and reacted at 60°C for 27 min to obtain silicone-modified polyurethane-acrylate resin.
[0039] S7. Add 35 parts of hydroxyethyl acrylamide, 4 parts of nano hydroxyapatite, 3 parts of PZ-33, 0.02 parts of BYK-028, and 0.03 parts of BYK-346 to silicone-modified polyurethane-acrylate resin. Stir for 9 minutes at room temperature and 125 r / min, and let stand to obtain scratch-resistant formaldehyde-free impregnating emulsion for decorative paper.
[0040] The base paper is impregnated and dried using the above-mentioned anti-scratch formaldehyde-free impregnated decorative paper impregnation emulsion to obtain impregnated film paper; the impregnated decorative paper is hot-pressed onto the surface of the artificial board to obtain decorative paper-faced artificial board.
[0041] Example 4 A method for preparing an impregnation emulsion for scratch-resistant, formaldehyde-free impregnated decorative paper: S1. Add 35 parts of polyethylene glycol and 35 parts of hexamethylene diisocyanate to a reactor equipped with a stirrer and a reflux device, and carry out a prepolymerization reaction under the protection of 99.9% nitrogen gas at a reaction temperature of 55°C for 0.8 h to obtain a polyurethane prepolymer.
[0042] S2. Heat the polyurethane prepolymer to 75°C, add ethylene glycol dropwise to the prepolymer over 18 min, the chain extension reaction lasts 1.4 h, and the stirring speed is 80 r / min. Then cool to 55°C and add 11 parts of N-methyldiethanolamine over 29 min, the reaction lasts 1.4 h.
[0043] S3. Cool to room temperature, add 0.4 parts of glacial acetic acid for neutralization, and simultaneously use 2 parts of acetone to reduce viscosity. Once the viscosity is suitable, add 18 parts of deionized water and 3 parts of organosilicon (composed of 1.5 parts of tetraethoxysilane and 1.5 parts of vinyltrimethoxysilane), and shear at high speed (3500 r / min). Evaporate and remove acetone to obtain the organosilicon-modified polyurethane emulsion. The emulsion has a solid content of 36%, a particle size of 90 nm, a viscosity of 90 cp, and a molecular weight of 1500.
[0044] S4. Add 0.15 parts ammonia water, 35 parts deionized water, 14 parts methyl acrylate, 24 parts acrylonitrile, 3 parts hydroxyethyl acrylate, 0.08 parts sodium persulfate, 9 parts sodium dodecyl sulfate and 13 parts NP-15 to the reactor, and keep the stirring speed at 190 r / min at room temperature for 9 min. Stop the reaction immediately after the color turns blue to obtain a polyacrylate preemulsion. S5. Mix the remaining 24 parts methyl acrylate, 24 parts acrylonitrile, and 6 parts hydroxyethyl acrylate evenly. At 83°C, add the mixture dropwise to the polyacrylate preemulsion along with the remaining sodium persulfate. While maintaining a stirring speed of 220 r / min, raise the temperature to 83°C and begin adding the remaining 6 parts organosilicon (composed of 3 parts tetraethoxysilane and 3 parts vinyltrimethoxysilane). The addition is completed in 38 min. After completion, maintain the temperature for 28 min to obtain the organosilicon-modified acrylate emulsion. The solid content of the emulsion is 36%, the particle size is 89 nm, the viscosity is 80 cp, and the molecular weight is 1800.
[0045] S6. The prepared silicone-modified polyurethane emulsion and silicone-modified polyacrylate emulsion are mixed and reacted at 65°C for 28 minutes to obtain silicone-modified polyurethane-acrylate resin.
[0046] S7. Add 38 parts acrylamide, 7 parts nano hydroxyapatite, 4 parts PZ-33, 0.02 parts BYK-028, and 0.04 parts BYK-346 to silicone-modified polyurethane-acrylate resin. Stir for 9 minutes at room temperature and 140 r / min, and let stand to obtain scratch-resistant formaldehyde-free impregnated decorative paper impregnation emulsion.
[0047] The base paper is impregnated and dried using the above-mentioned anti-scratch formaldehyde-free impregnated decorative paper impregnation emulsion to obtain impregnated film paper; the impregnated decorative paper is hot-pressed onto the surface of the artificial board to obtain decorative paper-faced artificial board.
[0048] Comparative Example 1 Using the impregnation resin system described in Example 1 of ZL202010394895.7, the decorative base paper is impregnated to obtain impregnated film paper; the impregnated decorative paper is hot-pressed onto the surface of the artificial board to obtain a decorative paper-faced artificial board.
[0049] Comparative Example 2 Using the impregnation resin system of Example 1 described in ZL202010394935.8, the decorative base paper is impregnated to obtain impregnated film paper; the impregnated decorative paper is hot-pressed onto the surface of the artificial board to obtain a decorative paper-faced artificial board.
[0050] Performance testing: The relevant physical properties of the impregnated decorative paper in Examples 1-4 and Comparative Examples 1-2 were tested according to national standards GB / T 28995-2012 and GB / T 15102-2017. The test results are shown in Table 1 below: Table 1 Comparison of physical properties of impregnated decorative paper and veneered artificial board
[0051] Compared with the published formaldehyde-free adhesives for decorative paper (Comparative Examples 1 and 2), the decorative papers in Examples 1-4 prepared using the impregnation emulsion of this invention not only show no release of free formaldehyde, but also have higher adhesive loading, better paper permeability, and better surface bonding strength, scratch resistance, and abrasion resistance, all meeting the requirements of relevant national standards. The organosilicon in the adhesive formulation reduces the particle size and adhesive strength of the impregnation adhesive, while nano-hydroxyapatite acts as a reinforcing material, increasing the adhesive absorption and surface hardness of the formaldehyde-free impregnated decorative paper, thereby achieving scratch resistance.
[0053] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A scratch-resistant, formaldehyde-free impregnating emulsion for decorative paper, characterized in that, Includes the following components: The composition includes 50-70 parts of silicone-modified polyurethane-acrylate resin, 30-40 parts of acrylamide monomers, 2-8 parts of nano-hydroxyapatite, 2-5 parts of curing agent, 0.01-0.03 parts of defoamer, and 0.01-0.05 parts of substrate wetting agent. The preparation method of the organosilicon-modified polyurethane-acrylate resin includes the following steps: S1. Add 20-40 parts of diol and 16-40 parts of diisocyanate to a reactor equipped with a stirrer and reflux device, and carry out a prepolymerization reaction under the protection of 99.9% nitrogen gas at a reaction temperature of 40-60℃ for 0.5-1h to obtain a polyurethane prepolymer. S2. Heat the polyurethane prepolymer to 65-80℃, add the chain extender dropwise over 10-20 minutes, and allow the chain extension reaction to proceed for 0.5-1.5 hours while stirring at 50-100 rpm. Then cool the prepolymer to 40-60℃ and add 8-12 parts of hydrophilic agent over 25-30 minutes. This step of the reaction should take 0.5-1.5 hours. S3. Cool to room temperature, add 0.1-0.5 parts of glacial acetic acid for neutralization, and simultaneously use 1-3 parts of acetone to reduce viscosity. Once the viscosity is suitable, add 15-20 parts of deionized water and 1.7-3.3 parts of organosilicon, and shear at high speed (2000-4000 r / min). Evaporate and remove acetone to obtain organosilicon-modified polyurethane emulsion. The solid content of the emulsion is 33-37%, the particle size is 50-100 nm, the viscosity is 50-100 cp, and the molecular weight is 500-2000. S4. Add 0.1-0.2 parts ammonia water, 25-40 parts deionized water, 10-15 parts soft acrylate monomer, 20-25 parts hard acrylate monomer, 1.7-3.3 parts hydroxy acrylate monomer, 0.03-0.1 parts initiator, 5-10 parts anionic surfactant and 6-14 parts nonionic surfactant to the reactor. Maintain a stirring speed of 150-200 r / min at room temperature and react for 7-10 min. Stop the reaction immediately after the color turns bluish to obtain a polyacrylate preemulsion. S5. Mix the remaining 20-25 parts of soft acrylate monomer, 20-25 parts of hard acrylate monomer, and 3.3-6.7 parts of hydroxyl acrylic monomer evenly. Under the condition of 75-85℃, add them dropwise to the polyacrylate preemulsion along with the remaining initiator. While maintaining a stirring speed of 150-240r / min, heat to 75-85℃ and start adding the remaining 3.3-6.7 parts of organosilicon. The addition is completed in 30-40min. After completion, keep the reaction temperature for 15-30min to obtain the organosilicon modified acrylate emulsion. The solid content of the emulsion is 33-37%, the particle size is 50-100nm, the viscosity is 20-100cp, and the molecular weight is 300-2000. S6. Mix the prepared silicone-modified polyurethane emulsion and silicone-modified polyacrylate emulsion, and react them at a temperature of 50-70℃ for 25-30 minutes to obtain silicone-modified polyurethane-acrylate resin.
2. The impregnation emulsion for scratch-resistant, formaldehyde-free impregnated decorative paper according to claim 1, characterized in that, The acrylamide monomer is one or more of acrylamide, hydroxymethylacrylamide, and hydroxyethylacrylamide; the curing agent is aziridine; and the defoamer is polyether silicone oil.
3. The impregnation emulsion for scratch-resistant, formaldehyde-free impregnated decorative paper according to claim 1, characterized in that, The nano-hydroxyapatite has a particle size of 20-80 nm.
4. The impregnation emulsion for scratch-resistant, formaldehyde-free impregnated decorative paper according to claim 1, characterized in that, The organosilicon-modified polyurethane-acrylate resin comprises the following components by weight: 16-40 parts diisocyanate, 20-40 parts diol, 40-50 parts hard acrylate monomer, 30-40 parts soft acrylate monomer, 5-10 parts hydroxyl acrylic monomer, 0.1-0.5 parts glacial acetic acid, 3-8 parts chain extender, 8-12 parts hydrophilic agent, 0.1-0.3 parts initiator, 5-10 parts anionic surfactant, 6-14 parts nonionic surfactant, 5-10 parts organosilicon, 40-60 parts deionized water, 0.1-0.2 parts ammonia, and 1-3 parts acetone.
5. The impregnation emulsion for scratch-resistant, formaldehyde-free impregnated decorative paper according to claim 4, characterized in that, The diol is one or more of polyethylene glycol, polypropylene glycol, and polyester diol; the diisocyanate includes one or more of isophorone diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, hexamethylene diisocyanate, and lysine diisocyanate.
6. The impregnation emulsion for scratch-resistant, formaldehyde-free impregnated decorative paper according to claim 4, characterized in that, The acrylate hard monomer includes one or more of methyl methacrylate, acrylic acid, methacrylic acid, and acrylonitrile; the acrylate soft monomer includes one or more of methyl acrylate, butyl acrylate, and n-octyl acrylate; the hydroxyacrylate monomer is one of hydroxyethyl acrylate, hydroxybutyl acrylate, and dihydroxypropyl acrylate.
7. The impregnation emulsion for scratch-resistant, formaldehyde-free impregnated decorative paper according to claim 4, characterized in that, The chain extender is one of ethylene glycol, propylene glycol, and 1,4-butanediol; the hydrophilic agent is N-methyldiethanolamine; the initiator is one of sodium persulfate, ammonium persulfate, and potassium persulfate; and the anionic surfactant is sodium dodecyl sulfate.
8. The impregnation emulsion for scratch-resistant, formaldehyde-free impregnated decorative paper according to claim 4, characterized in that, The nonionic surfactant is one or more of NP-15, A-103, and X-405.
9. The impregnation emulsion for scratch-resistant, formaldehyde-free impregnated decorative paper according to claim 4, characterized in that, The organosilicon comprises two or more of tetraethoxysilane, vinyltrimethoxysilane, and methylγ-mercaptopropyldimethoxysilane.
10. The method for preparing an impregnation emulsion for scratch-resistant formaldehyde-free impregnated decorative paper according to claim 1, characterized in that, Includes the following steps: Add 30-40 parts of acrylamide monomers, 2-8 parts of nano-hydroxyapatite, 2-5 parts of curing agent, 0.01-0.03 parts of defoamer, and 0.01-0.05 parts of substrate wetting agent to silicone-modified polyurethane-acrylate resin. Stir for 8-10 minutes at room temperature and 100-150 r / min, and let stand to obtain scratch-resistant formaldehyde-free impregnated decorative paper impregnation emulsion.
Citation Information
Patent Citations
Formaldehyde-free decorative adhesive film paper and preparation method thereof
CN109457536A
Formaldehyde-free adhesive for paper impregnated thermosetting resin and preparation method of adhesive
CN111411543A
A formaldehyde-free impregnating adhesive for decorative paper and its preparation method
CN111501416B